2021
DOI: 10.23917/ijolae.v3i3.13872
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Explanatory Investigation in using ICTs on Arabic Language and Islamic Values Education: Teacher-Students Perspective

Abstract: This study aims to see the extent of the application of ICT in the ALIVE program at Munoz Central School, as well as its effectiveness in the use of ICT. Furthermore, this study uses a mixed methods research design with a sequential explanatory approach. The sample of this study were students who took the ALIVE pro-gram at Munoz Central School. Quantitative and qualitative results indicate that the implementation of ICT in the ALIVE program is already good, it can be seen from the utilization of some ICT featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In connection to this, by the help of this formula, the results of each Skewness and Kurtosis z-value is computed and displayed in Table 4.3 as the following: From the above table, the statistic and standard error of skewness and kurtosis identified that if the data were normally distributed. According to the verification given by Doane & Seward (2011); Ikhlas et al (2021); Obumneke Ezie (2021);Onyeiwu et al (2021), when the statistic of kurtosis z-value of each variable is divided to its standard error and its result falls somewhere in the span of -1.96 and +1.96 which is the z-value, then we can conclude that the data is normally distributed which works for skewness too. Otherwise if the output is somewhere outside of the noted span, it is not normally distributed which encourages the use of non-parametric statistics.…”
Section: Data Testingmentioning
confidence: 80%
See 1 more Smart Citation
“…In connection to this, by the help of this formula, the results of each Skewness and Kurtosis z-value is computed and displayed in Table 4.3 as the following: From the above table, the statistic and standard error of skewness and kurtosis identified that if the data were normally distributed. According to the verification given by Doane & Seward (2011); Ikhlas et al (2021); Obumneke Ezie (2021);Onyeiwu et al (2021), when the statistic of kurtosis z-value of each variable is divided to its standard error and its result falls somewhere in the span of -1.96 and +1.96 which is the z-value, then we can conclude that the data is normally distributed which works for skewness too. Otherwise if the output is somewhere outside of the noted span, it is not normally distributed which encourages the use of non-parametric statistics.…”
Section: Data Testingmentioning
confidence: 80%
“…According to Ikhlas et al (2021); Obumneke Ezie (2021); Onyeiwu et al ( 2021), normality distribution of data by the help of the results of skewness and kurtosis, Kolmogorov-Smirnov and other criteria have to be thoroughly tested. In this context, the results of all the issues have shown that the data is not normally distributed.…”
Section: Data Testingmentioning
confidence: 99%
“…From the use of Elista as a medium in carrying out the process of completing the final project for lecturers as supervisors and students, from the test results, it can be seen that the lecturer's response is strongly influenced by several factors and is affected by technology (Rahman and Hundal, 2021). The novelty of this study is that this study discusses the response of the supervisor based on the gender of the supervisor (Ikhlas et al, 2021). In this study, guidance is carried out between lecturers and students through a website-based system called Elista (Hermita et al, 2022).…”
Section: Lecturer Gender Perspective With Online Thesis Guidance Case...mentioning
confidence: 95%
“…This digitalization era must help educators rekindle the enthusiasm of students to learn and simplify the learning process, of course with good educator knowledge about the technology itself (Hamidah et al, 2021). Because with the help of technology, learning becomes easier, active, and efficient (Ikhlas, Kuswanto, Sakunti, et al, 2021). Technology allows users to access information that is not limited by space and time.…”
Section: Introductionmentioning
confidence: 99%